Peningkatan Prestasi Belajar Matematika Melalui Penerapan Lesson Plan Berbasis Multiple Intelligence - Kristanto, Vigih Hery (Al-Jabar: Jurnal Pendidikan Matematika, 2017)
The purpose of this research is to find out in writing whether the mathematics achievement of students can be improved by the implementation of lesson plan based on Multiple Intelligence. This type of research is the study of literature with five steps, namely (1) collecting the literature and then do a review of some important terms in the study, (2) collecting relevant literature research result, (3) conducting in-depth analysis based on all the literature that has been obtained by the prepared discussion, (4) develop conclusions based on the analysis, (5) making recommendation based on the findings obtained. The conclusion of this research is that a written application of the lesson plan based on Multiple Intelligence has a tendency to increase student’s mathematics achievement.